City of women [compact disc, unabridged] - Gillham, David R. (Penguin Audio, 2012)
1943, in the height of World War II. With the men taken by the army, Berlin has become a city of women. While her husband fights on the Eastern Front, Sigrid Schroder is the model soldier's wife. She goes to work every day, does as much with her rations as she can, and cares for her meddling mother-in-law, all while ignoring the horrific immoralities of the regime. But behind the facade is an entirely different Sigrid. She dreams of her former Jewish lover, who is lost in the chaos of the war.